Svara Jiva Song: A Study of Educational Values in the Cultural Process of the antagonist of the Riau Rhythm group - Trigunawan, Ade; sunarto, Sunarto; Wadiyo, Wadiyo (Catharsis, 2020)
This study aims to analyze the educational values applied through the process of cultural antagonism to the "Svara Jiva" song of the Riau Rhythm group. This study used a qualitative method with an interdisciplinary approach to sociology and education. The data were collected by using observation, interview and document study techniques. The data analysis procedures used data reduction, data presentation, and data verification. The validity of the data used is triangulation, data sources and theory. The results showed that in the "Svara Jiva" song there was a cultural antagonistic process, namely a form of conflict within a creative individual with the culture, it caused a new form of cultural product. In the process of cultural antagonism, several educational values were implemented. The educational values included; 1) Religious Values; (2) Pluralist Value; (3) Historical Value; (4) Value of Responsibility; (5) Value of Responsibility. The results of this study can be used as a reference regarding the study of educational values.